2008
DOI: 10.1177/1538192707310509
|View full text |Cite
|
Sign up to set email alerts
|

Who Mentors Hispanic English Language Learners?

Abstract: Ten Hispanic university students enrolled in higher education courses were interviewed and considered successful despite the lack of support they received in learning English during their primary and secondary education. Analysis of the questionnaires and personal interviews reveal four major types of mentors who supported and motivated them to succeed throughout their post-high school education: family mentor, advisor mentor, self-mentor, and peer mentor.Resumen: Se entrevistaron diez estudiantes universitari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Another argument may be the motivation from others that might be fueling their desire to persist. De la Cruz (2008) argued that a salient aspect of support for LEP students is mentorship from a variety of sources: family, advisers, and peers. Perhaps the propensity to want to please and impress these supportive figures is implicitly and positively encouraging them to achieve.…”
Section: Discussionmentioning
confidence: 99%
“…Another argument may be the motivation from others that might be fueling their desire to persist. De la Cruz (2008) argued that a salient aspect of support for LEP students is mentorship from a variety of sources: family, advisers, and peers. Perhaps the propensity to want to please and impress these supportive figures is implicitly and positively encouraging them to achieve.…”
Section: Discussionmentioning
confidence: 99%
“…Institutions of secondary and higher education should look into ways to increase these mentor opportunities for Latino and other working class students. As research has shown that mentees are able to more easily relate to mentors who are the same gender, race, and ethnicity as they are, institutions should look to increase the number of Latino teachers and counselors who serve in schools with a primarily Latino student population mentorships (De La Cruz, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Although a growing number of studies exist examining which factors played a role in the success of academically successful Latinos, very few of these studies are quantitative in nature. The vast majority of the studies that have been conducted use a qualitative design and involve interviews of students which ask students to recall the factors that had the greatest impact on their education (Arellano & Padilla, 1996;Conchas, 2001;De La Cruz, 2008;Gonzales, 2010;Olivo, 2009;Sanchez, Reyes, & Singh, 2005;Stanton-Salazar & Spina, 2003). Some of these studies do involve surveys as part of their investigations; however these surveys tend to serve as a means of gathering demographic information and participant opinions rather than as tools to measure academic achievement (Arellano & Padilla, 1996;Kimura-Walsh et al, 2009;Olivo, 2009;Stanton-Salazar & Spina, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Another way in which scholars described immigrants positively within the U.S. higher education context was by demonstrating that this population often has high levels of motivation and resilience, despite structural inequalities and other barriers that they face in pursuing higher education (De La Cruz, 2008;Luna & Prieto, 2009;Morales et al, 2011;Tauriac & Liem, 2012). Similarly, articles focused on college access discussed immigrants having high college going and career aspirations (Arbelo-Marrero & Milacci, 2016;Griffin et al, 2012).…”
Section: Positive Depictionsmentioning
confidence: 99%